2013
DOI: 10.1002/pola.26807
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel hyperbranched polymers featuring oxazoline linear units and their application in fast‐drying solvent‐borne coating formulations

Abstract: Novel acid‐terminated hyperbranched polymers (HBPs) containing adipic acid and oxazoline monomers derived from oleic and linoleic acid have been synthesized via a bulk polymerization procedure. Branching was achieved as a consequence of an acid‐catalyzed opening of the oxazoline ring to produce a trifunctional monomer in situ which delivered branching levels of >45% as determined by 1H and 13C NMR spectroscopy. The HBPs were soluble in common solvents, such as CHCl3, acetone, tetrahydrofuran, dimethylformamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Via careful molecular design, vegetable oils or their derivatives can be introduced into HPs, which may present unique performance for end applications. [498][499][500] Two types of castor oil-based HPUs, MHPU and CHPU, were prepared using castor oil/monoglyceride, 1,4-butane diol, PCL and TDI as reactants. 498 The MHPUs exhibited higher tensile strength, scratch hardness and gloss, as well as lower elongation at break than those of CHPUs.…”
Section: Hp-based Coatingsmentioning
confidence: 99%
“…Via careful molecular design, vegetable oils or their derivatives can be introduced into HPs, which may present unique performance for end applications. [498][499][500] Two types of castor oil-based HPUs, MHPU and CHPU, were prepared using castor oil/monoglyceride, 1,4-butane diol, PCL and TDI as reactants. 498 The MHPUs exhibited higher tensile strength, scratch hardness and gloss, as well as lower elongation at break than those of CHPUs.…”
Section: Hp-based Coatingsmentioning
confidence: 99%
“…In addition to their easy synthesis , their three‐dimensional dendritic structure confers them with many advantageous properties over traditional linear polymers such as their non‐aggregation, high solubility , and low viscosity. Considerable research attention has been devoted to hyperbranched polymers in recent years owing to their interesting properties, which makes them potential candidates for applications ranging from coatings , non‐linear optical materials , light‐emitting diodes and sensors to catalysis . Recently, Mahapatra et al reported the synthesis of hyperbranched polyurethane (HBPU)‐GO via click coupling of azide‐ functionalized GO and alkyne‐terminated polyurethane (PU).…”
Section: Introductionmentioning
confidence: 99%